Burn Eschar Stimulates Fibroblast and Adipose Mesenchymal Stromal Cell Proliferation and Migration but Inhibits Endothelial Cell Sprouting - Monsuur, Hanneke N. (Int J Mol Sci, 2017)
The majority of full-thickness burn wounds heal with hypertrophic scar formation. Burn eschar most probably influences early burn wound healing, since granulation tissue only forms after escharotomy. In order to investigate the effect of burn eschar on delayed granulation tissue formation, burn wound extract (BWE) was isolated from the interface between non-viable eschar and viable tissue. The influence of BWE on the activity of endothelial cells derived from dermis and adipose tissue, dermal fibroblasts and adipose tissue-derived mesenchymal stromal cells (ASC) was determined. It was found that BWE stimulated endothelial cell inflammatory cytokine (CXCL8, IL-6 and CCL2) secretion and migration. However, BWE had no effect on endothelial cell proliferation or angiogenic sprouting. Indeed, BWE inhibited basic Fibroblast Growth Factor (bFGF) induced endothelial cell proliferation and sprouting. In contrast, BWE stimulated fibroblast and ASC proliferation and migration. No difference was observed between cells isolated from dermis or adipose tissue. The inhibitory effect of BWE on bFGF-induced endothelial proliferation and sprouting would explain why excessive granulation tissue formation is prevented in full-thickness burn wounds as long as the eschar is still present. Identifying the eschar factors responsible for this might give indications for therapeutic targets aimed at reducing hypertrophic scar formation which is initiated by excessive granulation tissue formation once eschar is removed.